The first Portuguese Open Dialogue pilot project intervention - Tavares, Sofia; Ribeiro, Joana; Graça, Sofia; Araújo, Bruna; Puchivailo, Mariana; Pereira, João G. (Frontiers in Psychology, 2023)
In 2020, the Directorate General of Health (DGS), a central service of the Ministry of Health in Portugal, approved and co-financed the first Open Dialogue program in the country. The present report aims to demonstrate the preliminary results of the first year of the project, implemented in the northern interior region of Alentejo. During this period, 7 People at the Center of Concern (PCC) and 21 family members/social network received care through Open Dialogue. Four external social workers and psychologists were also involved in the project as members of the support network. A total of 160 network meetings were undertaken, reaching as much as 27 per month in the busiest periods. Based on a previous Italian Research Protocol, developed by Pocobello, Sehity and Ciliberto (non-published manuscript), quantitative and qualitative data were collected in/and after the clinical meetings involving PCC and their family/social network, through a multi-method approach: clinical history interview (e.g. generic research on sociodemographic data, duration of untreated symptoms, reasons for requesting help, possible hospitalizations and/or treatments/therapies) and self-report scales applied every 5 sessions (e.g. CORE-OM, BSI, GAF, LSNS-6). The preliminary results indicate an improvement in global functioning and the enlargement of social network size/support, a decrease in symptoms and a negative correlation between the number of sessions and the LSNS6. Medication use kept largely unchanged at the end of the project.